Elements substantiation of decision-making schemes for the management of prosocial and environmental corporate innovations of industrial enterprises - V. V. Degtyareva (Вестник университета)
The article presents the elements of support schemes for decision-making on the management of prosocial and environmental corporate innovations of industrial enterprises with a multimodal element base for building a process and openness of developments, as well as a closed version of innovation implementation a unimodal approach. The approach proposed by the author is based on the concepts of convergent innovations, as well as the Nexus methodology (in other words, the concept of connections). The identified elements of the schemes should help in making decisions about the implementation of innovations and make the right choice for the heads of industrial enterprises within the framework of the ESG concept and the current prosocial and pro-environmental corporate governance philosophy. The article used general logical methods such as analysis, synthesis, abstraction, generalization, idealization, analogy, modeling, logical, structural-functional methods and approaches; visualization methods in the form of a graphical representation of information on the issue under study. The result of the study was a reasonable presentation of decision-making schemes when introducing changes in two areas of innovation implementation aimed at rationalizing the use of natural capital and the transition to a prosocial and pro-environmental concept of corporate innovation management in industrial enterprises.